"Hierarchical" patterns of meaning in communication representatives of the Muslim community: a multimodal perspective - I. Nasibullovmmad, Kamil (2018)
This зфзук is inspired by the idea of the Russian philosopher and orientalist A.V. Smirnov about the need to distinguish between two fundamental orientations of human thinking: the procedural and the substantial logics. The concept of a “picture of the world”, which is basic in the theory of A.V. Smirnov, is based on the intuition inherent in people that the world, with all its diversity, behaves in a certain stable way, and has an intrinsic coherence. A.V. Smirnov relies on the methods of philosophical and historical Islamic world view, and also on linguistic analysis of grammatical forms of the Arabic language. The concept of “action” in procedural logic is a fundamental category. The paper implements an attempt to apply his ideas to conduct a specific socio-psychological study of the world’s picture of contemporary Muslims. At the beginning of the paper a summary of his main ideas reflected in his two works, is given. In the future, the way of transferring his analytical scheme from the level of philosophical abstraction to the level of analysis of the individual and social (group) phenomenon is determined on the basis of the theory of social constructionism by K. Dzherdzhen, the theory of frames by G. Beitson, I. Hoffman. The last part of the paper highlights and describes the “hierarchical” patterns of reframing, derived from the study of Muslim communication using qualitative methods and a multimodal approach.